Molten salt electrolyte with low melting point, high conductivity and high stability as well as preparation and application thereof
By optimizing the composition ratio and preparation process of LiCl, LiBr, KBr and KF, a molten salt electrolyte with low melting point, high conductivity and high stability was prepared, which solved the problem of insufficient performance of molten salt electrolytes in the existing technology and improved the performance and reliability of thermal batteries.
Patent Information
- Application Number
- CN202510981613.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-07-16
- Publication Date
- 2025-11-21
AI Technical Summary
Existing molten salt electrolytes cannot simultaneously achieve both low melting point and high conductivity, which limits the miniaturization and long-endurance design of high-end weapons and equipment, and fails to meet the needs of industrial applications.
A molten salt electrolyte with a melting point ≤320.0℃ and an ionic conductivity ≥1.95S/cm at 500.0℃ was prepared by using a molten salt electrolyte composed of LiCl, LiBr, KBr and KF in a specific molar ratio, through optimization of the component ratio, drying and dehumidification and mixing and melting under an inert atmosphere.
It achieves a reduction in melting point of 8.0-41.0℃, an increase in ionic conductivity of 0.10-0.22S/cm, improved thermal stability, significantly extended working time of thermal batteries, broadened operating temperature range, and reduced cost of insulation materials.
Smart Images

Figure CN120999151A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of molten salt thermal battery technology, specifically to a molten salt electrolyte with low melting point, high conductivity and high stability, and its preparation and application. Background Technology
[0002] Molten salt thermal batteries are a type of storage battery that uses molten salt as the electrolyte. Compared with conventional chemical batteries, they possess unique advantages such as short activation time, high specific energy, long storage life, low vapor pressure, and wide operating temperature range. They are widely used in military equipment such as missiles, bombs, artillery, and mines, playing an irreplaceable role in the military field. The performance of molten salt thermal batteries is crucial to the effectiveness and operation of weapon systems. The characteristics of the molten salt electrolyte directly determine the performance of the thermal battery. Therefore, developing high-performance electrolytes is one of the key technologies to ensure the reliable, stable, and efficient operation of military equipment using molten salt thermal batteries as a power source.
[0003] Currently, commonly used electrolytes for molten salt thermal batteries include LiCl-KCl, LiF-LiCl-LiBr, and LiCl-LiBr-KBr. LiCl-KCl electrolyte has a melting point of 353.0℃, which is suitable for use under general current density conditions. However, as the operating time of the thermal battery increases, Li... + / K + Changes in concentration ratio alter the melting point and ionic conductivity of the thermal battery, leading to reduced discharge performance and premature failure. LiF-LiCl-LiBr possesses advantages in high ionic conductivity and high ion mobility, meeting the requirements of high-current discharge. However, its high melting point (443.0℃) and high operating temperature impose stringent requirements on insulation materials, limiting its use as a long-life thermal battery. LiCl-LiBr-KBr has a lower melting point (320.0℃) and a wider eutectic range, but its relatively low ionic conductivity only supports thermal batteries with ordinary current densities. Existing molten salt electrolytes struggle to balance low melting point and high conductivity, limiting the miniaturization and long-endurance design of high-end weaponry and failing to meet current industrial application needs.
[0004] Current mainstream molten salt electrolyte design focuses on optimizing existing molten salt electrolyte systems (LiCl-KCl, LiF-LiCl-LiBr, LiCl-LiBr-KBr, etc.). For example, the Chinese patent application "A Low Eutectic Salt for Thermal Batteries" (Publication No. CN116960378A) proposes adding 16%-30% BaCl2 to the LiF-LiCl-LiBr system, lowering the melting point to 421.6℃, but the melting point of this electrolyte is still relatively high. Furthermore, the Chinese patent application "Low Melting Point, High Conductivity Molten Salt Electrolyte and its Preparation Method" (Publication No. CN101471446A) discloses a LiF-LiCl-LiBr-KBr-KCl-KF hexa-membered molten salt electrolyte with a melting point of 275.0-286.0℃; however, the conductivity also decreases accordingly, with a conductivity of only 1.18-1.25 S / cm at the melting point. Existing technologies have conducted extensive research on lowering the melting point of molten salt thermal battery electrolytes, but improvements in electrolyte conductivity remain limited, failing to simultaneously meet the requirements of low melting point and high conductivity for molten salt electrolytes. Therefore, there is an urgent need to develop a novel molten salt electrolyte with low melting point, high conductivity, and high stability to provide a critical power source for next-generation high-end guided weapons, aircraft, and other equipment. Summary of the Invention
[0005] To address the problems of high melting point or low ionic conductivity in existing molten salt electrolytes, this invention provides a molten salt electrolyte with low melting point, high conductivity, and high stability. Compared with existing binary and ternary molten salt electrolytes, the melting point is significantly lower and the ionic conductivity is increased.
[0006] Another objective of this invention is to provide a method for preparing the aforementioned low-melting-point, high-conductivity, and high-stability molten salt electrolyte.
[0007] Another object of the present invention is to provide applications of the above-mentioned low melting point, high conductivity and high stability molten salt electrolyte.
[0008] The present invention specifically adopts the following technical solutions to solve the above-mentioned technical problems:
[0009] A low-melting-point, high-conductivity, and high-stability molten salt electrolyte comprising the following molar percentage components: 10.0-30.0 mol% LiCl, 40.0-60.0 mol% LiBr, 5.0-35.0 mol% KBr, and 1.0-10.0 mol% KF.
[0010] The low-melting-point, high-conductivity, and high-stability molten salt electrolyte has a melting point ≤320.0℃ and an ionic conductivity ≥1.95S / cm at 500.0℃.
[0011] As a first preferred embodiment, it comprises the following components in molar percentages: 15.0 mol% LiCl, 55.0 mol% LiBr, 25.0 mol% KBr, and 5.0 mol% KF.
[0012] As a second preferred embodiment, it comprises the following components in molar percentages: 25.0 mol% LiCl, 46.0 mol% LiBr, 26.0 mol% KBr, and 3.0 mol% KF.
[0013] As a third preferred embodiment, it comprises the following components in molar percentages: 29.0 mol% LiCl, 49.0 mol% LiBr, 17.0 mol% KBr, and 5.0 mol% KF.
[0014] As a fourth preferred embodiment, it comprises the following components in molar percentages: 20.0 mol% LiCl, 50.0 mol% LiBr, 25.0 mol% KBr, and 5.0 mol% KF.
[0015] As a fifth preferred embodiment, it comprises the following components in molar percentages: 27.0 mol% LiCl, 48.0 mol% LiBr, 21.0 mol% KBr, and 4.0 mol% KF.
[0016] A method for preparing a molten salt electrolyte as described in any of the above technical solutions includes the following steps: grinding and mixing LiCl, LiBr, KBr, and KF according to their molar percentages until homogeneous; heating to 360.0-560.0℃ at a heating rate of 1.0-10.0℃ / min and holding at this temperature for 1.0-10.0h, continuously introducing an inert atmosphere and stirring the molten salt to ensure homogeneity; and finally cooling to room temperature to obtain the molten salt electrolyte.
[0017] The purity of the raw materials LiCl, LiBr, KBr, and KF is all higher than 99.0%. Before mixing, the raw materials LiCl, LiBr, KBr, and KF are dried to remove water. Drying refers to drying at 130.0-350.0℃ for 10.0-36.0h. The inert atmosphere is either Ar or N2.
[0018] As described above, the preparation method of molten salt electrolyte is preferably carried out in an inert atmosphere glove box, where the water and oxygen content of the inert atmosphere glove box is less than 1.0 ppm, and the crucible used is a graphite or glassy carbon crucible.
[0019] The above-mentioned molten salt electrolytes are used in molten salt thermal batteries, fuel cells, and molten salt energy storage.
[0020] Compared with the prior art, the technical solution of the present invention has the following beneficial effects:
[0021] This invention, using low-cost LiCl, LiBr, KBr, and KF as raw materials, proposes and prepares for the first time a LiCl-LiBr-KBr-KF molten salt electrolyte with a melting point of 316.0±4.0℃, an ionic conductivity of not less than 1.95 S / cm at 500.0℃, and a decomposition temperature higher than 800.0℃ through optimized component ratios, drying and dehumidification, mixing and melting under an inert atmosphere, and constant-temperature homogenization. The molten salt electrolyte of this invention has a melting point 8.0-41.0℃ lower than that of existing classic molten salt electrolytes, an ionic conductivity at least 0.10-0.22 S / cm higher, and significantly improved thermal stability. It solves the problems of high melting point, low ionic conductivity, and low thermal stability of existing thermal battery molten salt electrolytes, providing a molten salt electrolyte with excellent comprehensive performance for molten salt thermal batteries, fuel cells, and molten salt energy storage, and has significant application value. Attached Figure Description
[0022] Figure 1 This is the DSC curve of Example 1;
[0023] Figure 2 This is the DSC curve of Example 2;
[0024] Figure 3 This is the DSC curve of Example 3;
[0025] Figure 4 This is the DSC curve of Example 4;
[0026] Figure 5 This is the DSC curve of Example 5;
[0027] Figure 6 This is the DSC curve for comparison 1;
[0028] Figure 7 This is the DSC curve for Comparative Example 2;
[0029] Figure 8 This is the DSC curve for Comparative Example 3;
[0030] Figure 9 This is a linear graph of the working electrode and the molten salt resistance in Example 1;
[0031] Figure 10 This is the mass change curve of Example 1 with temperature. Detailed Implementation
[0032] To facilitate public understanding, the technical solution of the present invention will be described in detail below through several specific embodiments and in conjunction with the accompanying drawings:
[0033] Sample and equipment pretreatment: Anhydrous LiCl, LiBr, KBr, and KF with a purity higher than 99.0% were stored in a glove box (covered with a high-purity inert Ar atmosphere, with water and oxygen content below 1.0 ppm) for later use; the electronic balance, high-temperature resistance furnace, and other backup equipment in the glove box were tested; the glassy carbon crucible was ultrasonically cleaned with deionized water, dried in an oven, and transferred to the glove box covered with a high-purity inert atmosphere; the experimental equipment in the glove box, such as crucible tongs, mortar and pestle, tweezers, self-sealing bags, and loading containers, were ensured to be dry and kept clean.
[0034] Example 1
[0035] In a glove box, LiCl, LiBr, KBr, and KF were placed into glassy carbon crucibles and covered with glassy carbon crucible lids. Then, they were transferred to a high-temperature resistance furnace and heated at a rate of 6.0℃ / min. The crucibles were kept at 200.0℃ for 12.0h to remove any residual moisture in the molten salt.
[0036] After adjusting the electronic balance (accuracy 0.001g), weigh out 15.0 mol% LiCl, 55.0 mol% LiBr, 25.0 mol% KBr, and 5.0 mol% KF after drying. Mix them thoroughly and place them in a clean glassy carbon crucible. Transfer the glassy carbon crucible, covered with a glassy carbon crucible lid, to a high-temperature resistance furnace and heat it to 480.0℃ at a heating rate of 8.0℃ / min. Hold the temperature for 7.0h, then pour out the molten salt and allow it to cool naturally to room temperature to obtain the quaternary LiCl-LiBr-KBr-KF molten salt electrolyte.
[0037] The prepared molten salt electrolyte sample was tested using differential scanning calorimetry (DSC). The test temperature range was RT-450.0℃, the heating rate was 10.0℃ / min, and the inert gas flow rate during the test was 60.0 mL / min. The DSC results are as follows: Figure 1 As shown, the melting point of the molten salt electrolyte in this embodiment is 312.0℃ and the enthalpy of fusion is 162.4J / g.
[0038] The ionic conductivity of the molten salt electrolyte prepared in this embodiment was tested using the continuously varying cell constant method. At 500.0°C, the distance of the working electrode within the molten salt electrolyte was moved, and a linear graph of the resistance between the working electrode and the molten salt electrolyte was obtained. The test results are shown below. Figure 9 As shown, the ionic conductivity of the molten salt electrolyte in this embodiment is 1.98 S / cm at 500.0 °C.
[0039] The molten salt electrolyte sample of this embodiment was tested using a simultaneous thermal analyzer (STA). The test range was RT-900.0℃, the heating rate was 10.0℃ / min, and the inert gas flow rate during the test was 60.0 mL / min. The experimental results are as follows: Figure 10 As shown, the decomposition temperature of the molten salt electrolyte in this embodiment is 830.0℃.
[0040] Example 2
[0041] In a glove box, LiCl, LiBr, KBr, and KF were placed into glassy carbon crucibles and covered with glassy carbon crucible lids. Then, they were transferred to a high-temperature resistance furnace and heated at a rate of 6.0℃ / min. The crucibles were kept at 200.0℃ for 12.0h to remove any residual moisture in the molten salt.
[0042] After adjusting the electronic balance (accuracy 0.001g), weigh out 25.0 mol% LiCl, 46.0 mol% LiBr, 26.0 mol% KBr, and 3.0 mol% KF after drying. Mix them thoroughly and place them in a clean glassy carbon crucible. Transfer the glassy carbon crucible, covered with a glassy carbon crucible lid, to a high-temperature resistance furnace and heat it to 480.0℃ at a heating rate of 8.0℃ / min. Hold the temperature for 7.0h, then pour out the molten salt and allow it to cool naturally to room temperature to obtain the quaternary LiCl-LiBr-KBr-KF molten salt electrolyte.
[0043] The prepared molten salt electrolyte sample was tested using differential scanning calorimetry (DSC). The test temperature range was RT-450.0℃, the heating rate was 10.0℃ / min, and the inert gas flow rate during the test was 60.0 mL / min. The DSC results are as follows: Figure 2 As shown, the melting point of the molten salt electrolyte in this embodiment is 316.0℃ and the enthalpy of fusion is 111.3J / g.
[0044] The ionic conductivity of the molten salt electrolyte prepared in this embodiment was tested using the continuously varying cell constant method, and the ionic conductivity of the molten salt electrolyte in this embodiment at 500.0℃ was found to be 2.01 S / cm. The molten salt electrolyte sample of this embodiment was tested using a simultaneous thermal analyzer (STA), and the decomposition temperature of the molten salt electrolyte in this embodiment was found to be 830.0℃.
[0045] Example 3
[0046] In a glove box, LiCl, LiBr, KBr, and KF were placed into glassy carbon crucibles and covered with glassy carbon crucible lids. Then, they were transferred to a high-temperature resistance furnace and heated at a rate of 6.0℃ / min. The crucibles were kept at 200.0℃ for 12.0h to remove any residual moisture in the molten salt.
[0047] After adjusting the electronic balance (accuracy 0.001g), weigh out 29.0 mol% LiCl, 49.0 mol% LiBr, 17.0 mol% KBr, and 5.0 mol% KF after drying. Mix them thoroughly and place them in a clean glassy carbon crucible. Transfer the glassy carbon crucible, covered with a glassy carbon crucible lid, to a high-temperature resistance furnace and heat it to 480.0℃ at a heating rate of 8.0℃ / min. Hold the temperature for 7.0h, then pour out the molten salt and allow it to cool naturally to room temperature to obtain the quaternary LiCl-LiBr-KBr-KF molten salt electrolyte.
[0048] The prepared molten salt electrolyte sample was tested using differential scanning calorimetry (DSC). The test temperature range was RT-450.0℃, the heating rate was 10.0℃ / min, and the inert gas flow rate during the test was 60.0 mL / min. The DSC results are as follows: Figure 3 As shown, the melting point of the molten salt electrolyte in this embodiment is 315.0℃ and the enthalpy of fusion is 83.4J / g.
[0049] The ionic conductivity of the molten salt electrolyte prepared in this embodiment was tested using the continuously varying cell constant method, and the ionic conductivity of the molten salt electrolyte in this embodiment at 500.0℃ was found to be 2.39 S / cm. The molten salt electrolyte sample of this embodiment was tested using a simultaneous thermal analyzer (STA), and the decomposition temperature of the molten salt electrolyte in this embodiment was found to be 830.0℃.
[0050] Example 4
[0051] In a glove box, LiCl, LiBr, KBr, and KF were placed into glassy carbon crucibles and covered with glassy carbon crucible lids. Then, they were transferred to a high-temperature resistance furnace and heated at a rate of 6.0℃ / min. The crucibles were kept at 200.0℃ for 12.0h to remove any residual moisture in the molten salt.
[0052] After adjusting the electronic balance (accuracy 0.001g), weigh out 20.0 mol% LiCl, 50.0 mol% LiBr, 25.0 mol% KBr, and 5.0 mol% KF after drying. Mix them thoroughly and place them in a clean glassy carbon crucible. Transfer the glassy carbon crucible, covered with a glassy carbon crucible lid, to a high-temperature resistance furnace and heat it to 480.0℃ at a heating rate of 8.0℃ / min. Hold the temperature for 7.0h, then pour out the molten salt and allow it to cool naturally to room temperature to obtain the quaternary LiCl-LiBr-KBr-KF molten salt electrolyte.
[0053] The prepared molten salt electrolyte sample was tested using differential scanning calorimetry (DSC). The test temperature range was RT-450.0℃, the heating rate was 10.0℃ / min, and the inert gas flow rate during the test was 60.0 mL / min. The DSC results are as follows: Figure 4 As shown, the melting point of the molten salt electrolyte in this embodiment is 315.0℃, and the enthalpy of fusion is 164.2J / g.
[0054] The ionic conductivity of the molten salt electrolyte prepared in this embodiment was tested using the continuously varying cell constant method, and the ionic conductivity of the molten salt electrolyte in this embodiment at 500.0℃ was found to be 1.95 S / cm. The molten salt electrolyte sample of this embodiment was tested using a simultaneous thermal analyzer (STA), and the decomposition temperature of the molten salt electrolyte in this embodiment was found to be 830.0℃.
[0055] Example 5
[0056] In a glove box, LiCl, LiBr, KBr, and KF were placed into glassy carbon crucibles and covered with glassy carbon crucible lids. Then, they were transferred to a high-temperature resistance furnace and heated at a rate of 6.0℃ / min. The crucibles were kept at 200.0℃ for 12.0h to remove any residual moisture in the molten salt.
[0057] After adjusting the electronic balance (accuracy 0.001g), weigh out 27.0 mol% LiCl, 48.0 mol% LiBr, 21.0 mol% KBr, and 4.0 mol% KF after drying. Mix them thoroughly and place them in a clean glassy carbon crucible. Transfer the glassy carbon crucible, covered with a glassy carbon crucible lid, to a high-temperature resistance furnace and heat it to 480.0℃ at a heating rate of 8.0℃ / min. Hold the temperature for 7.0h, then pour out the molten salt and allow it to cool naturally to room temperature to obtain the quaternary LiCl-LiBr-KBr-KF molten salt electrolyte.
[0058] The prepared molten salt electrolyte sample was tested using differential scanning calorimetry (DSC). The test temperature range was RT-450.0℃, the heating rate was 10.0℃ / min, and the inert gas flow rate during the test was 60.0 mL / min. The DSC results are as follows: Figure 5 As shown, the melting point of the molten salt electrolyte in this embodiment is 320.0℃, and the enthalpy of fusion is 194.8J / g.
[0059] The ionic conductivity of the molten salt electrolyte prepared in this embodiment was tested using the continuously varying cell constant method, and the ionic conductivity of the molten salt electrolyte in this embodiment at 500.0℃ was found to be 2.26 S / cm. The molten salt electrolyte sample of this embodiment was tested using a simultaneous thermal analyzer (STA), and the decomposition temperature of the molten salt electrolyte in this embodiment was found to be 830.0℃.
[0060] The above embodiments all yielded molten salt electrolytes with low melting point, high conductivity, and high stability. To verify the rationality and accuracy of the proposed low melting point, high conductivity, and high stability molten salt electrolyte composition, the following comparative experimental tests were further conducted:
[0061] Comparative Example 1
[0062] In a glove box, LiCl, LiBr, KBr, and KF were placed into glassy carbon crucibles and covered with glassy carbon crucible lids. Then, they were transferred to a high-temperature resistance furnace and heated at a rate of 6.0℃ / min. The crucibles were kept at 200.0℃ for 12.0h to remove any residual moisture in the molten salt.
[0063] After adjusting the electronic balance (accuracy 0.001g), weigh out 30.0 mol% LiCl, 18.0 mol% LiBr, 33.0 mol% KBr, and 19.0 mol% KF after drying. Mix them thoroughly and place them in a clean glassy carbon crucible. Transfer the glassy carbon crucible, covered with a glassy carbon crucible lid, to a high-temperature resistance furnace and heat it to 480.0℃ at a heating rate of 8.0℃ / min. Hold the temperature for 7.0h, then pour out the molten salt and allow it to cool naturally to room temperature to obtain the quaternary LiCl-LiBr-KBr-KF molten salt electrolyte.
[0064] The prepared molten salt electrolyte sample was tested using differential scanning calorimetry (DSC). The test temperature range was RT-450.0℃, the heating rate was 10.0℃ / min, and the inert gas flow rate during the test was 60.0 mL / min. The DSC results are as follows: Figure 6As shown, the melting point of the molten salt electrolyte in this comparative example was 339.0℃, and the enthalpy of fusion was 80.7 J / g. The ionic conductivity of the molten salt electrolyte prepared in this comparative example was tested using the continuously varying conductivity cell constant method, and the ionic conductivity at 500.0℃ was found to be 1.35 S / cm. The decomposition temperature of the molten salt electrolyte sample prepared in this comparative example was tested using a simultaneous thermal analyzer (STA), and the result was found to be 810.0℃.
[0065] Comparative Example 2
[0066] In a glove box, LiCl, LiBr, KBr, and KF were placed into glassy carbon crucibles and covered with glassy carbon crucible lids. Then, they were transferred to a high-temperature resistance furnace and heated at a rate of 6.0℃ / min. The crucibles were kept at 200.0℃ for 12.0h to remove any residual moisture in the molten salt.
[0067] After adjusting the electronic balance (accuracy 0.001g), weigh out 35.0 mol% LiCl, 5.0 mol% LiBr, 37.0 mol% KBr, and 23.0 mol% KF after drying. Mix them thoroughly and place them in a clean glassy carbon crucible. Transfer the glassy carbon crucible, covered with a glassy carbon crucible lid, to a high-temperature resistance furnace and heat it to 480.0℃ at a heating rate of 8.0℃ / min. Hold the temperature for 7.0h, then pour out the molten salt and allow it to cool naturally to room temperature to obtain the quaternary LiCl-LiBr-KBr-KF molten salt electrolyte.
[0068] The prepared molten salt electrolyte sample was tested using differential scanning calorimetry (DSC). The test temperature range was RT-450.0℃, the heating rate was 10.0℃ / min, and the inert gas flow rate during the test was 60.0 mL / min. The DSC results are as follows: Figure 7 As shown, the melting point of the molten salt electrolyte in this comparative example was 348.0℃, and the enthalpy of fusion was 64.7 J / g. The ionic conductivity of the molten salt electrolyte prepared in this comparative example was tested using the continuously varying conductivity cell constant method, and the ionic conductivity at 500.0℃ was found to be 1.11 S / cm. The decomposition temperature of the molten salt electrolyte sample in this comparative example was tested using a simultaneous thermal analyzer (STA), and the result was 810.0℃.
[0069] Comparative Example 3
[0070] In a glove box, LiCl, LiBr, KBr, and KF were placed into glassy carbon crucibles and covered with glassy carbon crucible lids. Then, they were transferred to a high-temperature resistance furnace and heated at a rate of 6.0℃ / min. The crucibles were kept at 200.0℃ for 12.0h to remove any residual moisture in the molten salt.
[0071] After adjusting the electronic balance (accuracy 0.001g), weigh out 30.0 mol% LiCl, 14.0 mol% LiBr, 33.0 mol% KBr, and 23.0 mol% KF after drying. Mix them thoroughly and place them in a clean glassy carbon crucible. Transfer the glassy carbon crucible, covered with a glassy carbon crucible lid, to a high-temperature resistance furnace and heat it to 480.0℃ at a heating rate of 8.0℃ / min. Hold the temperature for 7.0h, then pour out the molten salt and allow it to cool naturally to room temperature to obtain the quaternary LiCl-LiBr-KBr-KF molten salt electrolyte.
[0072] The prepared molten salt electrolyte sample was tested using differential scanning calorimetry (DSC). The test temperature range was RT-450.0℃, the heating rate was 10.0℃ / min, and the inert gas flow rate during the test was 60.0 mL / min. The DSC results are as follows: Figure 8 As shown, the melting point of the molten salt electrolyte in this comparative example was 349.0℃, and the enthalpy of fusion was 74.7 J / g. The ionic conductivity of the molten salt electrolyte prepared in this comparative example was tested using the continuously varying conductivity cell constant method, and the ionic conductivity at 500.0℃ was found to be 1.25 S / cm. The decomposition temperature of the molten salt electrolyte sample in this comparative example was tested using a simultaneous thermal analyzer (STA), and the result was 810.0℃.
[0073] The melting point, electrical conductivity (500.0℃), and decomposition temperature of Examples 1-5 of the present invention, Comparative Examples 1-3, LiCl-KCl (molar percentages of LiCl and KCl are 58.8 mol% and 41.2 mol%), LiF-LiCl-LiBr (molar percentages of LiF, LiCl, and LiBr are 22.0 mol%, 31.0 mol%, and 47.0 mol%), and LiCl-LiBr-KBr (molar percentages of LiCl, LiBr, and KBr are 25.0 mol%, 37.0 mol%, and 38.0 mol%) are shown in Table 1 below.
[0074] Table 1
[0075]
[0076]
[0077] In summary, the molten salt electrolyte obtained by this invention has a melting point of 316.0±4.0℃, an ionic conductivity of not less than 1.95 S / cm at 500.0℃, and a decomposition temperature of 830.0℃. The melting point of the molten salt electrolyte of this invention is 8.0-41.0℃ lower than that of classic molten salt thermal battery electrolytes (LiCl-KCl, LiCl-LiBr-KBr), its ionic conductivity is at least 0.10-0.22 S / cm higher than that of LiCl-KCl and LiCl-LiBr-KBr, and its thermal decomposition temperature is higher than 800.0℃. These superior properties of the molten salt electrolyte can effectively reduce the cost of insulation materials used in thermal batteries, significantly extend the working time of thermal batteries, and broaden the operating temperature range of molten salt thermal batteries. However, when the ratio of LiCl, LiBr, KBr, and KF is not within the scope protected by this invention (refer to Comparative Examples 1-3), the melting point increases and the ionic conductivity decreases significantly, resulting in reduced charging and discharging efficiency and stability of the thermal battery, which directly affects the safety and service life of the thermal battery.
[0078] The above embodiments are only some implementations of the present invention. In practical applications, the technical solutions of the present invention can be reasonably adjusted according to specific conditions, including but not limited to changes in raw material ratios and optimization of process parameters. Any improved solution based on the technology of the present invention, as long as its technical features are the same as or similar to the technical solutions described in the claims of the present invention, should be considered to fall within the protection scope of the present invention.
Claims
1. A molten salt electrolyte, characterized in that, It comprises the following components in molar percentages: 10.0-30.0 mol% LiCl, 40.0-60.0 mol% LiBr, 5.0-35.0 mol% KBr, and 1.0-10.0 mol% KF.
2. The molten salt electrolyte according to claim 1, characterized in that, It comprises the following components in molar percentage: 15.0 mol% LiCl, 55.0 mol% LiBr, 25.0 mol% KBr, and 5.0 mol% KF.
3. The molten salt electrolyte according to claim 1, characterized in that, It comprises the following components in molar percentage: 25.0 mol% LiCl, 46.0 mol% LiBr, 26.0 mol% KBr, and 3.0 mol% KF.
4. The molten salt electrolyte according to claim 1, characterized in that, It comprises the following components in molar percentage: 29.0 mol% LiCl, 49.0 mol% LiBr, 17.0 mol% KBr, and 5.0 mol% KF.
5. The molten salt electrolyte according to claim 1, characterized in that, It comprises the following components in molar percentage: 20.0 mol% LiCl, 50.0 mol% LiBr, 25.0 mol% KBr, and 5.0 mol% KF.
6. The molten salt electrolyte according to claim 1, characterized in that, It comprises the following components in molar percentage: 27.0 mol% LiCl, 48.0 mol% LiBr, 21.0 mol% KBr, and 4.0 mol% KF.
7. The molten salt electrolyte according to claim 1, characterized in that, The molten salt electrolyte has a melting point ≤320.0℃ and an ionic conductivity ≥1.95S / cm at 500.0℃.
8. A method for preparing a molten salt electrolyte according to any one of claims 1 to 7, characterized in that, LiCl, LiBr, KBr, and KF are ground and mixed in molar percentage until homogeneous; then heated to 360.0-560.0℃ at a heating rate of 1.0-10.0℃ / min and held at this temperature for 1.0-10.0h. During the holding process, an inert atmosphere is continuously introduced and the molten salt is stirred to ensure homogeneity. Finally, the mixture is cooled to room temperature to obtain the molten salt electrolyte.
9. The method for preparing molten salt electrolyte according to claim 8, characterized in that, The inert atmosphere is either Ar or N2, and the water and oxygen content in the reaction system is both below 1.0 ppm; the purity of the raw materials LiCl, LiBr, KBr, and KF is all above 99.0%; the raw materials LiCl, LiBr, KBr, and KF are dried to remove water before mixing, which means drying at 130.0-350.0℃ for 10.0-36.0 h.
10. The application of the molten salt electrolyte according to any one of claims 1 to 7 in the fields of molten salt thermal batteries, fuel cells and molten salt energy storage.
Citation Information
Patent Citations
Low-melting-point high-conductivity molten salt electrolyte and preparation method thereof
CN101471446A
Eutectic salt for thermal battery
CN116960378A